2015
DOI: 10.1007/s13277-015-3112-0
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal onco-miRs from serum of patients with adenocarcinoma of the esophagus: comparison of miRNA profiles of exosomes and matching tumor

Abstract: Diagnostic markers are needed for achieving a cure in esophageal cancer, detecting tumor cells earlier. Exosomes are bioactive vesicles secreted by cells into surrounding body fluids. Exosome formation, cargo content, and delivery have major impact in cancer development. This is the first isolation of exosomes from serum of patients with adenocarcinoma of the esophagus and comparison of exosomal miRNA profiles with matching primary tumor and normal tissues. RNA was extracted for miRNA profiling by real-time Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
73
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 53 publications
5
73
0
Order By: Relevance
“…We found that although we unified the amount of cel-miR-39, cel-miR-39 expression showed significant differences in different experiments. We then compared some internal references according to previous reports, such as miR-16 [28-32], U6 [32-34], and miR-451 [21]. We found that miR-451b was stably expressed in serum exosomes without any significant difference between patients with DCM-AHF and the CG (Table 2).…”
Section: Discussionmentioning
confidence: 93%
“…We found that although we unified the amount of cel-miR-39, cel-miR-39 expression showed significant differences in different experiments. We then compared some internal references according to previous reports, such as miR-16 [28-32], U6 [32-34], and miR-451 [21]. We found that miR-451b was stably expressed in serum exosomes without any significant difference between patients with DCM-AHF and the CG (Table 2).…”
Section: Discussionmentioning
confidence: 93%
“…One of the downregulated microRNAs, miR-126-5p have been proven to be involved in the carcinogenesis and development of various types of cancer in previous studies [7782]. …”
Section: Discussionmentioning
confidence: 99%
“…These miRNAs regulate cell growth and differentiation, and play important roles in the process of life and the development of disease (Cheng et al , 2015; Das et al , 2014; Duan et al , 2014). Studies indicate that miRNAs are closely related to the occurrence and development of tumors (Warnecke-Eberz et al , 2015; Wong et al , 2011; Ye et al , 2013). It has been reported that miRNAs play an important role in the regulation of tumor in prostate, lung, breast and colon cancers.…”
Section: Introductionmentioning
confidence: 99%